PENGARUH BIBLIOTERAPY TERHADAP PENINGKATAN KREATIVITAS VERBAL PADA ANAK USIA SEKOLAH (Studi di SDN Bangunsari 02 Mejayan Madiun Jawa Timur) - YUSWATININGSIH, ENDANG; Ike Suhariati, Hindyah (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
The aim of this study was analyzing the influence of bibliotherapy on verbal enhancement in school-aged children.The design of this research is quasi-experimental research with one group pre test-post test design. The population in this study are all students of grade 4.5 and 6 SD Negeri Bangunsari 02 Mejayan with the number of samples of 34 respondents. Sampling technique in this research is probability sampling with proportionate stratified random sampling. Data collection by giving questionnaires before and after given bibliotherapy. Data processing with editing, coding, scoring and tabulating. Analysis using  two t sample statistic test paired with error rate 5% (0,05).The results showed that before given bibliotherapy the average score for verbal creativity was 94.08 with a standard deviation of 9.80. After being given bibliotherapy the average score for verbal creativity was 99.88 with a standard deviation of 8.80. The result of the analysis showed p value (0,001) and this is smaller than alpha 0,05 so H1 accepted.The conclusion in this study is that there is an influence of bibliotherapy to increase verbal creativity in school age children.Keywords:bibliotherapy, verbal creativity, school-age